Understanding customers' continuous intention to use of social commerce via Facebook: a theoretical model and empirical examination. (13th July 2021) - Herzallah, Fadi; Ayyash, Mohannad Moufeed
The current study proposes a model examining the impact of expectation-confirmation model-IS factors in combination with social commerce constructs to better understand the incentives behind customers' continued use of social commerce via Facebook in Palestine. The proposed model was tested by administering a survey to a number of 218 customers. The data was analysed using structural equation modelling (SEM). The findings revealed that perceived usefulness and social commerce constructs positively impact customers' satisfaction and continuous intention to use. Moreover, expectations of confirmation positively influence satisfaction and perceived usefulness. Customers' satisfaction positively impacts continuous intention to use; satisfaction is a more powerful determinant of continuous intention to use than perceived usefulness and S-commerce constructs. The findings can be used by social commerce service providers in formulating strategies toward proliferation of customers' continuous intention to use and can be useful for scholars to increase, improve and assess research on social commerce field.